Evaluasi Penerapan Akuntansi Manajemen Lingkungan dalam Pengelolaan Program Kerja pada Dinas Lingkungan Hidup Kabupaten Bangkalan (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aims to evaluate the application of environmental management accounting in the management of work programs at the Bangkalan Regency Environmental Agency. The research is motivated by increasing environmental problems, particularly waste volume and limited management facilities, while environmental management accounting has the potential to assist agencies in identifying, measuring, and reporting environmental costs as a basis for decision-making and public accountability. This study used a qualitative method with a case study approach at the Bangkalan Regency Environmental Agency. Data were collected through interviews, observations, and documentation studies. The results show that the Environmental Agency has implemented environmental management accounting, but its recording is still manual and does not separate environmental costs from general operational costs. This condition complicates cost evaluation and program impact assessment. Work program management has been structured and evaluated regularly, but performance measurement still focuses on output, not long-term environmental impact. Information transparency is also still limited to activity publications. Overall, the application of environmental accounting is at a basic stage and has not been fully integrated into the work program planning and evaluation process. The findings of this study provide theoretical and practical implications in the form of strengthening understanding of the role of environmental management accounting and the need to improve the work program recording and evaluation system at the Bangkalan Regency Environmental Agency.